Trichilemmal Carcinoma on the Head (Surgical Challenge to Achieve Free Margin): A Case Report - Daan Khambri (National Cancer Center - Dharmais Cancer Hospital, 2022)
Introduction: Trichilemmal carcinoma is a rare tumor derived from the outer hair sheath. It usually appears on the face, ears, neck, scalp, and sun-exposed areas. It generally occurs in patients older than 50 years old, and there is no sex predilection to this disease.Case Presentation: A 60-year-old woman came with a complaint of a lump in the head that often bled. The size of the lump was approximately like a bean seed and broke when she combed her hair. The lump was getting bigger within a year and easier to bleed. She often felt pain. Based on the history of surgery 2 months ago, the examination implies that the patient had trichilemmal carcinoma.Conclusions: Trichilemmal carcinoma generally occurs in the elderly category. Although trichilemmal carcinoma has a benign clinical course and local recurrence cases are uncommon, sufficient free margin and immediate reconstruction are challenging if the predilection is in the head and neck. Surgical excision is the recommended treatment for this disease